The Brasilia Rules and the rights of the child or adolescent in the procedural sphere - Bermúdez Tapia, Manuel (2021)
In recent years, the Brasilia Rules have enhanced the judicial and procedural parameters because they have regulated mechanisms for legal action in favor of persons in vulnerable situations. Consequently, they receive better attention in the protection of their rights. In effect, the Brasilia Rules improve the particular and special conditions of these persons. Special evaluation elements include: gender perspective, assistance to persons with disabilities, protection of the rights and interests of children and adolescents, guardianship of unprotected migrants, as well as a multicultural and bilingual perspective. These elements are the premises with which judicial systems in Latin America seek to efficiently address the demands that develop in their jurisdictions. As a general standard of reference, the purposes of the Brasilia Rules appear to improve the justice administration system. However, a more detailed analysis of the judicial context and procedural participation, and the evaluation of judicialized family conflicts involving children and adolescents, allows us to detail some conditions that require more special attention. In particular, civil procedural rules should take into account the human context and the circumstances in which children find themselves in the middle of a judicial process where their parents are the main actors.